Accuracy of office hysteroscopy in the diagnosis of chronic endometritis - Mohamed Elmahdy Abdel Moneim; Amany Abdelbary Abdel Latif; Marwa Said Shehata; Ibrahim Abdel Latif Ghanem (Clinical and Experimental Obstetrics & Gynecology)
Background: To test the accuracy of office hysteroscopy in the diagnosis of chronic endometritis (CE) as compared to histopathological diagnosis. Methods: This prospective cohort study was conducted in a private hospital from July 2018 to January 2020. 220 infertile women were scheduled for first attempt of intracytoplasmic sperm injection (ICSI). Patients ranging in age from 20–40 with history of primary infertility scheduled for ICSI for the first time were included, while patients with chronic diseases, severe vaginal bleeding, previous failed ICSI, polycystic ovary syndrome (PCOS), or endometriosis were excluded. All patients received postmenstrual office hysteroscopy to rule out the presence of CE; at the same setting, endometrial biopsy was taken and sent for histopathological examination. Results: 174 cases (79.1%) were diagnosed as CE at hysteroscopy, while 162 (73.6%) cases were positive at histopathology. 99.4% of the cases presented with hyperaemia, followed by oedema in 74.7% and micro-polypi in 58.6% of cases with CE. There was a significant difference between the hysteroscopic and the histopathologic diagnosis of CE (p < 0.001). The sensitivity, specificity, and positive and negative predictive values of hysteroscopy were 93.83%, 62.07%, 87.36% and 78.26% respectively. Conclusions: Office hysteroscopic evaluation is relatively accurate on its own but can be further confirmed by CD138 staining.